PELAKSANAAN KEGIATAN EKSTRAKURIKULER NASYID DI MADRASAH ALIYAH NEGERI 2 PADANG - Muhammad Faldi Al-Amin; Tulus Handra Kadir; Syahrel Syahrel (SENDRATASIK UNP, 2016)
This article aims to find out about the design and implementation of extracurricular activities nasyid MAN 2 Padang. The discussion is focused on how the implementation of extracurricular activities at this time nasyid makes Nasyid performance MAN 2 Padang decreased every Nasyid Festival among students. This type of research is qualitative research. The subjects studied were Nasyid Extracurricular Activities in MAN 2 Padang. Data was collected through observation and documentation. In this study, the instrument is the researchers themselves, with the support instrument documentation tools. The research results can be explained that the success of an extracurricular activity depends on good design in these extracurricular activities, as well as extracurricular activities nasyid. In addition to the plan, in extracurricular activities nasyid be accompanied by the implementation of good to get a result and performance on target.